Respuesta :
slope formula;
m = y2 - y1/ x2 - x1 (-3, 6), (0, -8)
m = -8 - 6/ 0 - (-3)
m = -14/3
hope this helps, God bless!
m = y2 - y1/ x2 - x1 (-3, 6), (0, -8)
m = -8 - 6/ 0 - (-3)
m = -14/3
hope this helps, God bless!
the formula suppose to look like this
y₂ - y₁
-------
x₂ - x₁
it doesn't matter which one you choose first, just make sure you plug in the last one correctly
so if i choose (0, -8) as my "₂", then it will look like
-8 - 6
--------
0 - (-3)
-8 - 6/ 0 - (-3)
-14/3
-14/3 should be your slope
hope this helps
y₂ - y₁
-------
x₂ - x₁
it doesn't matter which one you choose first, just make sure you plug in the last one correctly
so if i choose (0, -8) as my "₂", then it will look like
-8 - 6
--------
0 - (-3)
-8 - 6/ 0 - (-3)
-14/3
-14/3 should be your slope
hope this helps